2022
DOI: 10.1186/s42408-022-00143-6
|View full text |Cite
|
Sign up to set email alerts
|

Fire history and vegetation data reveal ecological benefits of recent mixed-severity fires in the Cumberland Mountains, West Virginia, USA

Abstract: Background Without periodic fire, fire-adapted plant communities across the Central Hardwood Forest Region (CHF) in the USA have undergone significant changes in forest structure and species composition, most notably a decrease in oak regeneration and herbaceous diversity and an increase in shade-tolerant, fire-sensitive tree species. In this study, we conducted a comparative analysis of two mixed pine-oak (Pinus-Quercus) forests with different land management histories in the Cumberland Mounta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
3
0
1
Order By: Relevance
“…El fuego es un proceso biofísico que interviene en la distribución de especies y ecosistemas terrestres. Evolutivamente, las interacciones entre el clima, la vegetación y el uso antropogénico de la tierra han determinado las características -como frecuencia, intensidad, patrones de consumo del combustible, extensión espacial y el momento estacional-y los mecanismos de adaptación a los regímenes de incendios (Jardel Peláez et al, 2014;Keeley et al, 2011;Saladyga et al, 2022).…”
Section: El Fuego En El Paisaje Mexicanounclassified
“…El fuego es un proceso biofísico que interviene en la distribución de especies y ecosistemas terrestres. Evolutivamente, las interacciones entre el clima, la vegetación y el uso antropogénico de la tierra han determinado las características -como frecuencia, intensidad, patrones de consumo del combustible, extensión espacial y el momento estacional-y los mecanismos de adaptación a los regímenes de incendios (Jardel Peláez et al, 2014;Keeley et al, 2011;Saladyga et al, 2022).…”
Section: El Fuego En El Paisaje Mexicanounclassified
“…Such a transformation has extensive ecological implications, as oaks play a keystone role in biotic and abiotic ecosystem processes (Fralish 2004) With the aim of curtailing these forest changes, land managers have reintroduced re primarily through prescribed burning, or burning combined with thinning treatments (P. Brose et al 2001). However, there is a growing recognition of the ecological bene ts of incorporating attributes of wild re into management plans (Ryan et al 2013), particularly for restoring re-dependent species and alleviating oak-pine recruitment issues (Black et al 2018;Saladyga et al 2022). Wild re events often create a heterogeneous mosaic of burn severity (Hutchinson et al 2008) that prompts a greater range of ecological responses than prescribed res, which are typically lower in severity and more spatially homogenous (P. Brose et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Patches with increased burn severity are more likely to experience decreased density and basal area in the midstory and overstory initially following a re, which increases understory light availability (Reilly et al 2006). These changes to forest structure are essential for promoting the establishment and growth of understory pyrophytic species (Kuddes-Fischer and Arthur 2002), and have been shown to directly increase the recruitment of oak (Black et al 2018) and pine (Black et al 2018;Saladyga et al 2022) saplings. At our research site in the Cumberland Plateau, Black et al (2018) found that increased burn severity bolstered the competitive status of oaks and pines in the understory at six years post-re.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation